2013
DOI: 10.1007/s12160-012-9433-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual- and Area-Level Disparities in Access to the Road Network, Subway System and a Public Bicycle Share Program on the Island of Montreal, Canada

Abstract: Background Few studies have examined potential disparities in access to transportation infrastructures, an important determinant of population health. Purpose To examine individual-and area-level disparities in access to the road network, public transportation system, and a public bicycle share program in Montreal, Canada. Methods Examining associations between sociodemographic variables and access to the road network, public transportation system, and a public bicycle share program, 6,495 adult respondents (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…availability of bicycles stations around home), and education. Fuller et al (2013a) showed that PBSP accessibility was greater for Montreal' residents living in loweducation and low-income areas, and in areas with environmental characteristics favouring cycling. Therefore, greater awareness of PBSP was expected for these populations given their proximity to bicycles docking station.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…availability of bicycles stations around home), and education. Fuller et al (2013a) showed that PBSP accessibility was greater for Montreal' residents living in loweducation and low-income areas, and in areas with environmental characteristics favouring cycling. Therefore, greater awareness of PBSP was expected for these populations given their proximity to bicycles docking station.…”
Section: Discussionmentioning
confidence: 99%
“…trains, bus, car) have historically modified healthy lifestyle (Hallal et al, 2012), recent transport-related facilities such as public bicycle share programs (PBSP) can promote active transportation (Fuller et al, 2013c;Ogilvie et al, 2012;Torres et al, 2013). Despite PBSP's promising health benefits (Fuller et al, 2012;Torres et al, 2013;Woodcock et al, 2014), accessibility is limited by the location of docking stations (Fuller et al, 2013a;Ogilvie et al, 2012;Webster and Cunningham, 2013) and by financial barriers related to cost of use (Buck, 2012;Fishman et al, 2012). Although some additional efforts have been made to increase the availability to PBSP for low-income populations, these actions may not be sufficient (Kretman Stewart et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Montreal’s BIXI (BIcycle-taXI) program, North America’s largest in 2012, makes available 5050 bicycles at 405 docking stations within an area with a population density of approximately 12,000 residents/km 2 [23]. The PBSP is implemented in areas with good access to public transportation in the form of subway and bus service [24]. PBSPs are understudied.…”
mentioning
confidence: 99%
“…In fact, the distribution of resources and of physical environment characteristics are neither socially nor politically neutral (Harvey, 1973, Soja, 2010. For instance, mobility opportunities such as public transit routes, bike paths, and access to highways may not be distributed equally across urban spaces (Miciukiewicz and Vigar, 2012), though this may depend on the layout of a given city (Fuller et al, 2013). Individual and geographic characteristics, as well as access conditions, thus interact to enable or impede certain social groups' possible mobilities.…”
Section: Daily Mobility Potential: An Unequally Distributed Resourcementioning
confidence: 99%